2021
DOI: 10.21203/rs.3.rs-639611/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preoperative C-reactive Protein-to-albumin Ratio Predicts Anastomotic Leakage After Esophagectomy for Thoracic Esophageal Cancer: a Single-center Retrospective Cohort Study

Abstract: Background: Postoperative anastomotic leakage (AL) is associated with not only prolonged hospital stay and increased medical costs, but also poor prognosis in esophageal cancer. Several studies have addressed the utility of various inflammation-based and/or nutritional markers as predictors for postoperative complications. However, none have been documented as specific predictors for AL in esophageal cancer. We aimed to identify predictors of AL after esophagectomy for thoracic esophageal cancer, focusing on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…Likewise, Sugimoto et al. have reported that preoperative CAR was a significant predictor for anastomotic leakage after esophagectomy for thoracic esophageal cancer, but CRP or albumin alone was not 32 . Moreover, similar results were observed in the current study (CAR was significantly associated with severe ED, whereas CRP or albumin alone was not).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Likewise, Sugimoto et al. have reported that preoperative CAR was a significant predictor for anastomotic leakage after esophagectomy for thoracic esophageal cancer, but CRP or albumin alone was not 32 . Moreover, similar results were observed in the current study (CAR was significantly associated with severe ED, whereas CRP or albumin alone was not).…”
Section: Discussionsupporting
confidence: 90%
“…have reported that preoperative CAR was a significant predictor for anastomotic leakage after esophagectomy for thoracic esophageal cancer, but CRP or albumin alone was not. 32 Moreover, similar results…”
Section: Discussionsupporting
confidence: 58%
“…Several inflammation-based biomarkers have been used to predict the mortality and morbidity of various cancers undergoing antitumor therapies (8,9). Among these biomarkers, the albumin and neutrophil-to-lymphocyte ratio (NLR) has been extensively investigated for use in HNC (10,11).…”
mentioning
confidence: 99%